Experimental study of wind pressure fluctuating characteristics and wind load shape factor of long‐span cylinder roof structure. (20th May 2021) - Wu, Yanru; Wu, Xiaohong; Wei, Sitong; Sun, Qing; Wang, Jiantao
Summary: This paper comprehensively presents the results of a wind tunnel experiment of the wind pressure fluctuating characteristics of a long‐span roof structure, namely the fluctuating wind pressure coefficient (FWPC), wind pressure power spectrum, and wind pressure coherence. The variation trend of FWPCs in the wind directions of 0°, 45°, and 90° were analyzed in sealed and open conditions, as well as the fluctuating wind pressure coefficients of lateral and longitudinal profiles of roof. Subsequently, the models of wind pressure spectrum in different zones and the spatial coherence of fluctuating wind pressure at different wind angles were discussed. The zone values of wind load shape factors of envelope structure with sealed, open, and pile of coal in open were calculated by area weighted averaging. The results indicate that the sealed condition significantly influences the fluctuating characteristics on the roof surface more than the open condition, suggesting that the maximum varied gradient of FWPCs is achieved in the 45° wind direction. Further, different forms and peak frequencies of the wind pressure spectrum in the roof region developed three zones, revealing that the peak frequency in energy‐preserved, inertia, and energy‐dissipated regions show an increasing trend for the different directions. The spatial correlations of wind pressure between measurement taps decrease with the increase in the frequency and spatial distance. Moreover, the correlation coefficients are lower than 0.2 when the frequency was higher than 35 Hz, and a modified three‐dimensional spatial coherence function of wind pressure is proposed. In contrast to the sealed case, the zone values of wind load shape factors of envelope structure with open and pile of coal in open are alleviated due to the separation flows.